A biomimetic nanoplatform for customized photothermal therapy of HNSCC evaluated on patient-derived xenograft models - Qi Wu; Lan Chen; Xiaojuan Huang; Jiayi Lin; Jiamin Gao; Guizhu Yang; Yaping Wu; Chong Wang; Xindan Kang; Yanli Yao; Yujue Wang; Mengzhu Xue; et al. (Nature Publishing Group, 2023)
Abstract Cancer cell membrane (CCM) derived nanotechnology functionalizes nanoparticles (NPs) to recognize homologous cells, exhibiting translational potential in accurate tumor therapy. However, these nanoplatforms are majorly generated from fixed cell lines and are typically evaluated in cell line-derived subcutaneous-xenografts (CDX), ignoring the tumor heterogeneity and differentiation from inter- and intra- individuals and microenvironments between heterotopic- and orthotopic-tumors, limiting the therapeutic efficiency of such nanoplatforms. Herein, various biomimetic nanoplatforms (CCM-modified gold@Carbon, i.e., Au@C-CCM) were fabricated by coating CCMs of head and neck squamous cell carcinoma (HNSCC) cell lines and patient-derived cells on the surface of Au@C NP. The generated Au@C-CCMs were evaluated on corresponding CDX, tongue orthotopic xenograft (TOX), immune-competent primary and distant tumor models, and patient-derived xenograft (PDX) models. The Au@C-CCM generates a photothermal conversion efficiency up to 44.2% for primary HNSCC therapy and induced immunotherapy to inhibit metastasis via photothermal therapy-induced immunogenic cell death. The homologous CCM endowed the nanoplatforms with optimal targeting properties for the highest therapeutic efficiency, far above those with mismatched CCMs, resulting in distinct tumor ablation and tumor growth inhibition in all four models. This work reinforces the feasibility of biomimetic NPs combining modular designed CMs and functional cores for customized treatment of HNSCC, can be further extended to other malignant tumors therapy.